ANALYSIS THE IMPLEMENTATION OF QUALITY AND ENVIRONMENTAL MANAGEMENT IN PETROCHEMICAL INDUSTRIES - Virna Amaral (ENVIROSAN : Jurnal Teknik Lingkungan, 2019)
The petrochemical industry produces useful products including plastics, synthetic rubber, solvents, fertilizers, pharmaceutical products, additives, explosives and adhesives, producing waste that can cause environmental problems in the production process. For this reason, industries must meet international standard and get the recognition that stating their quality and environmental management systems are in accordance with the standards. The international standards regarding quality and environmental management used are ISO 9001: 2015 and ISO 14001; 2015. This study aims to identify and compare good strategies from three Petrochemical companies in implementing ISO 9001; 2015 and ISO 14001; 2015. The data used is an annual report from the company regarding the application of the ISO. From the results shown the annual report that Indonesia is more clearly explained. Divided per section in detail and PT. Chandra Asri Petrochemicals and Indorama Ventures have implemented strategies that are in accordance with ISO 9001: 2015 and ISO 14001: 2015. In implementing ISO 9001: 2015 and ISO 14001: 2015, each company has its own strategy to be able to maintain market competitiveness and in creating the attractiveness of products by emphasizing the impact on environment. Annual report yang Indonesia lebih dijabarin jelas. Dibagi per bagian dengan detail dan PT. Chandra Asri Petrochemicals and Indorama Ventures telah menerapkan strategi yang sesuai dengan ISO 9001:2015 and ISO 14001:2015. Keywords: Petrochemical company,Quality management system, environmental management system.